2020
DOI: 10.1123/japa.2019-0251
|View full text |Cite
|
Sign up to set email alerts
|

Environmental Features Associated With Older Adults’ Physical Activity in Different Types of Urban Neighborhoods

Abstract: The authors studied associations of nature- and infrastructure-based features with physical activity (PA) in different urban neighborhood types; 848 community-dwelling people aged 75–90 years reported PA and three perceived nature-based destinations and seven infrastructure-based features as outdoor mobility facilitators. Neighborhood type was defined using a geographic information system based on proximity to central service areas and residential density (city center, subcenter, and dense and dispersed areas … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
7
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 7 publications
(8 citation statements)
references
References 30 publications
1
7
0
Order By: Relevance
“…The current findings accord with those of previous studies showing that perceiving environmental facilitators is associated with higher physical activity levels (Barnett et al, 2017; Cerin et al, 2017; Keskinen et al, 2019). Further support for environmental mobility facilitators as motivators of outdoor mobility was provided by the present multinomial logistic regression analysis.…”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…The current findings accord with those of previous studies showing that perceiving environmental facilitators is associated with higher physical activity levels (Barnett et al, 2017; Cerin et al, 2017; Keskinen et al, 2019). Further support for environmental mobility facilitators as motivators of outdoor mobility was provided by the present multinomial logistic regression analysis.…”
Section: Discussionsupporting
confidence: 93%
“…Participants were asked to report all the items present in their living environment that they perceived as facilitating their outdoor mobility (present/ absent). Environmental facilitators were categorized into three domains: nature (park or other green area, walking trail and skiing track, and nature and lakeside); infrastructure (good lighting, services close, even sidewalks, walkways without steep hills, resting places by the walking route, peaceful and good quality pedestrian routes, and safe crossings); and safety (appealing landscape, familiar surroundings, own yard, other people outdoors, no car traffic, and no cyclists on walkways) (Keskinen et al, 2019).…”
Section: Measurementsmentioning
confidence: 99%
“…For older persons, physical activity often accumulates while running daily errands such as going shopping and doing domestic chores [ 3 ]. Physical activity level may be dependent on urban design and infrastructure of neighborhoods as it has been shown that older adults are more active when living in neighborhoods with high walkability [ 4 ], residential density [ 5 , 6 ], and access to public transportation [ 7 ]. Maintaining physical activity in the older age groups is important for sustaining functional ability, independent living, and community participation [ 2 , 8 , 9 ].…”
Section: Introductionmentioning
confidence: 99%
“…Furthermore, sidewalks and streets in poor conditions were associated with a decreased likelihood of voting among those with mobility difficulty (Clarke et al, 2011). A recent study of older adults living in Finland found that the relationship between the quality of sidewalks and physical activity was dependent on neighborhood type (Keskinen et al, 2019). Evenness of sidewalks was associated with the likelihood of physical activity, but only among those living in areas outside of city centers and not within more densely populated environments (Keskinen et al, 2019).…”
Section: Introductionmentioning
confidence: 99%
“…A recent study of older adults living in Finland found that the relationship between the quality of sidewalks and physical activity was dependent on neighborhood type (Keskinen et al, 2019). Evenness of sidewalks was associated with the likelihood of physical activity, but only among those living in areas outside of city centers and not within more densely populated environments (Keskinen et al, 2019). Conversely, a longitudinal study within the South Holland city of Spijkenisse in the Netherlands found that sidewalk features were not associated with self-reported difficulty in activities of daily living (ADL) or outdoor active transport (i.e., walking or cycling for transport) among older adults aged 65 years and older, after controlling for age and sex (Etman et al, 2016).…”
Section: Introductionmentioning
confidence: 99%